DASAR PERLEMBAGAAN SEBAGAI PENCAPAIAN SULTAN MUDA OMAR ‘ALI SAIFUDDIEN DALAM SYAIR PERLEMBAGAAN NEGERI BRUNEI - Abd Ghani, Nurdiyana; Idris, Zubir (JURNAL MELAYU SEDUNIA, 2020)
The Constitution of Brunei State by Sultan Muda Omar ‘Ali Saifuddien is one of the documents of literary work that is very important and meaningful for Brunei Darussalam. Syair Perlembagaan Negeri Brunei, penned by the ruler of Brunei, Sultan Muda Omar ‘Ali Saifuddien, is one such poem. It records important events that surrounded the establishment of the Brunei State Constitution, as well as offers advice on providing leadership to the people and governing the country, all of which are addressed to His Majesty’s 'pakulun' (that is members of his family, namely his sons and daughters, especially the crown prince in line to the throne). His Majesty’s wisdom is evident in the three main subjects that he chose to treat in the poem. Firstly, the poem makes clear a royal prince’s visions and ambitions for his people; secondly, it records historical events that led to the establishment of Brunei’s Written Constitution; and thirdly, it offers advice, culled from His Majesty’s experience and leadership, which it presents in the form of parables. The strength and worth of the poem lies largely in the critical ideas and philosophy of royal leadership, one that envisions the country’s progress in the future. The author was also a nationalist and the country’s poet laureate who successfully ruled Brunei as its 28th sultan. The results of the study found that the Constitution of Brunei has been able to describe the achievements of Sultan Muda Omar ‘Ali Saifuddien in his efforts to fight for the constitutional policy of Brunei